The Process of Identifying Students with Special Needs in Inclusive Elementary Schools - Fadila, Tazkiya Indah; Sunardi, Sunardi (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
The identification process is the first step in determining the special needs of learners. This stage is important as a basis for conducting assessments and designing individual learning programs for learners with special needs. This research uses a qualitative descriptive method. Data collection was done through classical tests, observation and interviews. The data was presented in graphical form and then analyzed descriptively. The identification results showed 2 students with special needs. The types of special needs found are specific learning difficulties including dyslexia, dysgraphia and dyscalculia.